1985
DOI: 10.1177/0164027585007004005
|View full text |Cite
|
Sign up to set email alerts
|

Retirement Satisfaction in the Rural Elderly

Abstract: This study investigated factors related to retirement satisfaction in a Midwestern rural population. Four major sets of variables were investigated: personal background factors; socialization for retirement; reasons for retirement; and social integration. Multiple regression showed that the most important predictors of retirement satisfaction were (1) quality of relationship and frequency of aid from confidants and relatives; (2) involvement in organizations; (3) health; and (4) financial status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 33 publications
2
39
1
Order By: Relevance
“…It is popularly believed that retirement has a negative association with health (Crimmins, Saito & Reynolds, 1997;Reynolds, Crimmins, & Saito, 1998). In fact, many studies have shown that retirees who have been retired longer have a tendency to report more health problems than workers and retirees with less time in retirement, (e.g., Dorfman, Kohout, & Heckert, 1985;Rohwedder & Willis, 2010). This is especially the case for people who regard retirement as a stressful event, since this attitude could have psycho-social consequences such as depression and anxiety (Dave, Rashard & Spasojevic, 2008;Holmes & Rahe, 1967;Minkler, 1981;Nuttman-Shwarz, 2004).…”
Section: Consequences Of Retirementmentioning
confidence: 99%
“…It is popularly believed that retirement has a negative association with health (Crimmins, Saito & Reynolds, 1997;Reynolds, Crimmins, & Saito, 1998). In fact, many studies have shown that retirees who have been retired longer have a tendency to report more health problems than workers and retirees with less time in retirement, (e.g., Dorfman, Kohout, & Heckert, 1985;Rohwedder & Willis, 2010). This is especially the case for people who regard retirement as a stressful event, since this attitude could have psycho-social consequences such as depression and anxiety (Dave, Rashard & Spasojevic, 2008;Holmes & Rahe, 1967;Minkler, 1981;Nuttman-Shwarz, 2004).…”
Section: Consequences Of Retirementmentioning
confidence: 99%
“…Although the majority of the retirees cope well with retirement, poor adjusters consistently have emerged in studies conducted over the past 20 years in a number of developed countries (Braithwaite and Gibson, 1989). Studies done on satisfaction during retirement have found that important predictors of retirement satisfaction are quality of relationships and frequency of aid from confidants and relatives, involvement in organizations, and health and financial status (Dorfman et al, 1985). In particular, retirees with higher incomes or adequate finances reported being more satisfied with life in retirement (Crowley, 1986; Dorfman, 1992; Palmore, Fillenbaum, and George, 1984).…”
Section: Literature Reviewmentioning
confidence: 99%
“…People who have managed to work until old age pension in good health show more positive life experiences in retirement than do those without these advantages (Dorfman 1995(Dorfman , 1985Kim and Moen 2001;McGoldrick and Cooper 1994;Mein et al 2003;Hyde et al 2004;Smith and Moen 2004;Pinquart and Schindler 2007). People who leave the labour market involuntarily, on the other hand, compelled by push factors such as health problems or as a result of environmental or structural constraints, are less likely to perceive retirement in positive terms (Nordenmark and Stattin 2009).…”
Section: Introductionmentioning
confidence: 99%